Adhesive composition for decorative film and decorative film
By using an adhesive composition containing a carboxyl monomer and a (meth)acrylic polymer with a specific glass transition temperature, the problem of insufficient adhesion and durability of the decorative film adhesive in a low temperature environment is solved, and good adhesion and durability are achieved, and it is suitable for use in vehicle decoration and other purposes.
Patent Information
- Application Number
- CN202411476825.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-08-28
- Filing Date
- 2024-10-22
- Publication Date
- 2025-04-29
AI Technical Summary
The prior art has not yet found a decorative film adhesive that can provide a good adhesion and excellent durability just after application under a low temperature environment.
A binder composition comprising a (meth)acrylic polymer having a predetermined structural unit and a polymer having a predetermined glass transition temperature is used. The (meth)acrylic polymer of the composition contains 1 to 20 mass% of the carboxyl group-containing monomer, the glass transition temperature of the polymer is between 30 to 200°C, and the number average molecular weight is between 500 to 10,000.
The adhesive composition for decorative film provided in a low temperature environment has good adhesion and durability, is suitable for surface decoration of various molded bodies, and is especially suitable for internal and external components of vehicles such as automobiles and trains.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive composition for a decorative film and a decorative film using the adhesive composition for a decorative film. Background Art
[0002] Due to the trend of reducing volatile organic compounds (VOC) in recent years, various automobile manufacturers are actively adopting decorative films with adhesive layers instead of exterior paint. The performance required of the adhesive used in the decorative film is that when the decorative film processed by bonding is applied to the adherend, in the case of positional displacement, a material with low viscosity is preferred in order to be able to be easily re-adhered. On the other hand, if the viscosity is too low, peeling will occur immediately after application, so it is also required to have a moderate adhesion. In particular, in low temperature environments such as cold regions, the viscosity becomes low, so the adhesion immediately after application tends to become insufficient.
[0003] Patent Document 1 discloses a decorative film having an adhesive layer containing a specific vinyl polymer and an acrylic adhesive polymer. Patent Document 2 discloses a decorative film having a pressure-sensitive adhesive layer and an acrylic resin film layer, wherein the pressure-sensitive adhesive layer contains a carboxyl group-containing (meth)acrylic polymer and a (meth)acrylic polymer having an amino group capable of forming a metal complex with metal ions generated from a metal substrate. Each of these decorative films has long-term stable adhesive strength and excellent durability.
[0004] However, the reality is that an adhesive for decorative films having good adhesion immediately after application and excellent durability has not yet been found.
[0005] Prior art literature Patent Literature [Patent Document 1: Japanese Patent Application Publication No. 2019-112574 [Patent Document 2: Japanese Patent No. 6574109 Summary of the invention Problem that the invention aims to solve An object of the present invention is to provide an adhesive composition for a decorative film having good adhesion immediately after application and excellent durability, and a decorative film using the adhesive composition for a decorative film.
[0006] Means used to solve problems The present inventors have conducted intensive studies in view of the above circumstances, and as a result have found that a PSA composition including a (meth)acrylic polymer having a predetermined structural unit and a polymer having a predetermined Tg can solve the above problems, thereby completing the present invention.
[0007] The present invention relates to, for example, the following [1] to [6].
[0008] [1] An adhesive composition for a decorative film, comprising a (meth)acrylic polymer (A) and a polymer (B), wherein the (meth)acrylic polymer (A) comprises 1 to 20% by mass of a structural unit derived from a carboxyl group-containing monomer, and the polymer (B) has a glass transition temperature of 30 to 200° C. and a number average molecular weight (Mn) of 500 to 10,000, and the polymer (B) is contained in an amount of 0.1 to 100 parts by mass per 100 parts by mass of the (meth)acrylic polymer (A).
[0009] [2] The adhesive composition for a decorative film according to [1], wherein the (meth)acrylic polymer (A) contains 6.5 to 20% by mass of a structural unit derived from an alkyl (meth)acrylate having a homopolymer glass transition temperature of less than -55°C.
[0010] [3] The adhesive composition for a decorative film according to [1] or [2], wherein the weight average molecular weight (Mw) of the (meth)acrylic polymer (A) is 200,000 or more and less than 800,000.
[0011] [4] The adhesive composition for a decorative film according to any one of [1] to [3], wherein the polymer (B) contains 65% by mass or more of a structural unit derived from methyl methacrylate.
[0012] [5] A decorative film comprising a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition for a decorative film according to any one of [1] to [4], and a substrate layer.
[0013] [6] The decorative film according to [5], which is used for vacuum pressurization (pressure air) molding.
[0014] Effects of the Invention According to the present invention, an adhesive composition for a decorative film having good adhesion and excellent durability immediately after application and a decorative film using the adhesive composition for a decorative film can be provided. The adhesive composition for a decorative film of the present invention can be suitably used for the adhesive layer of a decorative film, and the decorative film using the adhesive composition has good adhesion and excellent durability immediately after application. The decorative film according to the present invention can be used for surface decoration of various molded bodies, and can be particularly suitably used for decorative purposes of interior and exterior parts of vehicles such as automobiles and trains. DETAILED DESCRIPTION
[0015] Hereinafter, the present invention will be described in detail.
[0016] In the present invention, acrylic acid and methacrylic acid are also referred to as "(meth)acrylic acid", and acrylate and methacrylate are collectively referred to as "(meth)acrylate". In addition, in the present invention, A to B indicating a numerical range means A or more and B or less unless otherwise specified.
[0017] <Adhesive composition for decorative film> The adhesive composition for decorative films according to the present invention (hereinafter, also referred to as “the present composition”) is a composition containing a (meth)acrylic polymer (A), a polymer (B), and other components as required.
[0018] [(Meth)acrylic acid polymer (A)] The (meth)acrylic polymer (A) is a polymer containing a (meth)acrylic monomer as a main component and a monomer component (a) containing 1 to 20% by mass of a carboxyl group-containing monomer (a1). Here, the main component means a component containing more than 50% by mass in 100% by mass of the monomer component (a). The monomer component (a) may also use an alkyl (meth)acrylate (a2) and other monomers (a3) whose homopolymer has a glass transition temperature of less than -55°C.
[0019] The (meth)acrylic polymer (A) used in the present composition may be one kind or two or more kinds.
[0020] (Carboxyl group-containing monomer (a1)) Examples of the carboxyl group-containing monomer (a1) include carboxyl group-containing (meth)acrylates such as β-carboxyethyl (meth)acrylate, 5-carboxypentyl (meth)acrylate, mono(meth)acryloyloxyethyl succinate, and ω-carboxypolycaprolactone mono(meth)acrylate; monounsaturated fatty acids such as (meth)acrylic acid and crotonic acid; and diunsaturated fatty acids such as maleic acid, fumaric acid, itaconic acid, and citraconic acid, and their anhydrides. Among these, (meth)acrylic acid is preferred.
[0021] The carboxyl group-containing monomer (a1) may be used alone or in combination of two or more.
[0022] The content of the carboxyl group-containing monomer (a1) in 100% by mass of the monomer component (a) is 1 to 20% by mass, preferably 2 to 18% by mass, more preferably 3 to 16% by mass, and even more preferably more than 5% by mass and less than 15% by mass.
[0023] When the content of the carboxyl group-containing monomer (a1) is within the above range, excellent durability is likely to be obtained, which is preferred.
[0024] (Alkyl (meth)acrylate (a2) having a homopolymer glass transition temperature of less than -55°C) Examples of the (meth)acrylic acid alkyl ester (a2) having a homopolymer glass transition temperature of less than -55°C include n-hexyl acrylate (Tg: -57°C), n-octyl acrylate (Tg: -65°C), isooctyl acrylate (Tg: -58°C), 2-ethylhexyl acrylate (Tg: -70°C), nonyl acrylate (Tg: -58°C), and lauryl methacrylate (Tg: -65°C).
[0025] The (meth)acrylate alkyl ester (a2) having a homopolymer glass transition temperature of less than -55°C may be used alone or in combination of two or more.
[0026] In addition, in this invention, as the glass transition temperature of the homopolymer of each monomer, the value described in Polymer Handbook Forth Edition (Wiley-Interscience 2003) can be used, for example.
[0027] When the (meth)acrylate alkyl ester (a2) having a homopolymer glass transition temperature of lower than -55°C is used in 100% by mass of the monomer component (a), the content ratio thereof is usually 99% by mass or less, preferably 2 to 70% by mass, more preferably 4 to 40% by mass, and further preferably 6.5 to 20% by mass in 100% by mass of the monomer component (a).
[0028] When the (meth)acrylate (a2) having a homopolymer glass transition temperature of less than −55° C. is within the above range, the adhesiveness immediately after application tends to be excellent, which is preferred.
[0029] (Other monomers (a3)) The other monomer (a3) is a monomer other than the carboxyl group-containing monomer (a1) and the (meth)acrylic acid alkyl ester (a2) having a homopolymer glass transition temperature of lower than -55°C.
[0030] Examples of the other monomer (a3) include alkyl (meth)acrylates having a homopolymer glass transition temperature of not less than -55°C, alicyclic group-containing (meth)acrylates, aromatic ring-containing (meth)acrylates, alkoxyalkyl (meth)acrylates, alkoxypolyalkylene glycol mono(meth)acrylates, and crosslinkable functional group-containing monomers other than carboxyl group-containing monomers.
[0031] Examples of the (meth)acrylic acid alkyl esters having a homopolymer glass transition temperature of not less than -55°C include methyl acrylate (Tg: 8°C), ethyl acrylate (Tg: -24°C), n-propyl acrylate (Tg: 3°C), isopropyl acrylate (Tg: -3°C), n-butyl acrylate (Tg: -50°C), isobutyl acrylate (Tg: -40°C), tert-butyl acrylate (Tg: 43°C), n-pentyl acrylate (Tg: 22°C), lauryl acrylate (Tg: -3°C), methyl methacrylate (Tg: 105°C), ethyl methacrylate (Tg: 105°C), and tert-butyl acrylate (Tg: 22°C). 65℃), n-propyl methacrylate (Tg: 35℃), isopropyl methacrylate (Tg: 81℃), tert-butyl methacrylate (Tg: 118℃), n-butyl methacrylate (Tg: 20℃), isobutyl methacrylate (Tg: 48℃), n-pentyl methacrylate (Tg: -5℃), n-hexyl methacrylate (Tg: -5℃), n-octyl methacrylate (Tg: -20℃), isooctyl methacrylate (Tg: -45℃), 2-ethylhexyl methacrylate (Tg: -10℃), isodecyl methacrylate (Tg: -41℃).
[0032] Examples of the alicyclic group-containing (meth)acrylate include cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and adamantyl (meth)acrylate.
[0033] Examples of the aromatic ring-containing (meth)acrylate include benzyl (meth)acrylate, phenyl (meth)acrylate, and phenoxyethyl (meth)acrylate.
[0034] Examples of the alkoxyalkyl (meth)acrylate include 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, and 4-ethoxybutyl (meth)acrylate.
[0035] Examples of the alkoxypolyalkylene glycol mono(meth)acrylate include methoxydiethylene glycol mono(meth)acrylate, methoxydipropylene glycol mono(meth)acrylate, ethoxytriethylene glycol mono(meth)acrylate, ethoxydiethylene glycol mono(meth)acrylate, and methoxytriethylene glycol mono(meth)acrylate.
[0036] The alkyl (meth)acrylates, alicyclic group-containing (meth)acrylates, aromatic ring-containing (meth)acrylates, alkoxyalkyl (meth)acrylates, and alkoxypolyalkylene glycol mono(meth)acrylates having a homopolymer glass transition temperature of not less than -55°C may be used alone or in combination of two or more.
[0037] When such a monomer is used, the content ratio is usually 99 mass % or less, preferably 1 to 95 mass %, more preferably 2 to 90 mass %, and further preferably 3 to 85 mass % in 100 mass % of the monomer component (a).
[0038] Examples of the crosslinkable functional group-containing monomer other than the carboxyl group-containing monomer include a hydroxyl group-containing monomer, an amino group-containing monomer, an amide group-containing monomer, and a cyano group-containing monomer.
[0039] Examples of the hydroxyl group-containing monomer include hydroxyl group-containing (meth)acrylates, and specific examples include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and 8-hydroxyoctyl (meth)acrylate.
[0040] Examples of the amino group-containing monomer include N-alkylaminoalkyl (meth)acrylates such as N-methylaminoethyl (meth)acrylate and N-ethylaminoethyl (meth)acrylate.
[0041] Examples of the amide group-containing monomer include (meth)acrylamide, N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-propyl(meth)acrylamide, N-hexyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, and N,N-diethyl(meth)acrylamide.
[0042] Examples of the cyano group-containing monomer include (meth)acrylonitrile.
[0043] The crosslinkable functional group-containing monomer other than the carboxyl group-containing monomer may be used alone or in combination of two or more.
[0044] When a crosslinkable functional group-containing monomer other than a carboxyl group-containing monomer is used, its content is usually 20 mass % or less, preferably 15 mass % or less, more preferably 10 mass % or less, and further preferably 5 mass % or less in 100 mass % of the monomer component (a).
[0045] In addition, the (meth)acrylic polymer (A) according to the present invention may contain, in the monomer component (a), copolymerizable monomers such as nitrogen-containing heterocyclic monomers such as N-vinylpyrrolidone, N-vinylcaprolactam, and (meth)acryloylmorpholine, vinyl esters such as vinyl acetate and vinyl propionate, olefins such as ethylene, propylene, and isobutylene, halogenated olefins such as vinyl chloride and vinylidene chloride, styrene monomers such as styrene and α-methylstyrene, and diene monomers such as butadiene, isoprene, and chloroprene, within a range that does not impair its physical properties. When such copolymerizable monomers are used, the content ratio thereof is preferably 30% by mass or less, and more preferably 20% by mass or less, in 100% by mass of the monomer component (a).
[0046] [Method for producing (meth)acrylic acid-based polymer (A)] The (meth)acrylic polymer (A) is obtained by copolymerizing the above-mentioned monomer component (a). The production method is not particularly limited, and a known method can be used, for example, solution polymerization, bulk polymerization, emulsion polymerization, suspension polymerization, etc., and solution polymerization is preferred because the molecular weight can be easily adjusted and there are few impurities during production.
[0047] Specifically, a polymerization solvent, a monomer component (a), and, if necessary, a chain transfer agent are charged into a reaction vessel, a polymerization initiator is added under an inert gas atmosphere such as nitrogen, the reaction start temperature is usually set to 40 to 100° C., preferably 50 to 90° C., the reaction system is usually maintained at a temperature of 50 to 90° C., preferably 60 to 90° C., and the reaction is carried out for 3 to 20 hours to obtain a (meth)acrylic polymer (A).
[0048] Examples of the polymerization initiator include an azo-based initiator and a peroxide-based polymerization initiator.
[0049] Examples of the azo initiator include 2,2'-azobisisobutyronitrile, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2-cyclopropylpropionitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2-(carbamoylazo)isobutyronitrile, 2-phenylazo-4-methoxy-2,4-dimethylvaleronitrile, 2,2'-azobis(2-cyclopropylpropionitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2-(carbamoylazo)isobutyronitrile, 2-phenylazo-4-methoxy-2,4-dimethylvaleronitrile, Azo compounds of (2-amidinopropane) dihydrochloride, 2,2'-azobis(N,N'-dimethyleneisobutylamidine), 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)-propionamide], 2,2'-azobis(isobutylamide) dihydrate, 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-cyanopropanol), dimethyl-2,2'-azobis(2-methylpropionate), 2,2'-azobis(2-methyl-N-(2-hydroxyethyl)propionamide).
[0050] Examples of the peroxide-based polymerization initiator include tert-butyl hydroperoxide, cumene hydroperoxide, dicumyl peroxide, benzoyl peroxide, lauroyl peroxide, hexanoyl peroxide, diisopropyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, tert-butyl peroxydivalerate, 2,2-bis(4,4-di-tert-butylperoxycyclohexyl)propane, 2,2-bis(4,4-di-tert-amylperoxycyclohexyl)propane, 2,2-bis(4,4-di-tert-octylperoxycyclohexyl)propane, 2,2-bis(4,4-di-α-cumylperoxycyclohexyl)propane, 2,2-bis(4,4-di-tert-butylperoxycyclohexyl)butane, and 2,2-bis(4,4-di-tert-octylperoxycyclohexyl)butane.
[0051] The polymerization initiator may be used alone or in combination of two or more. There is no limitation on adding the polymerization initiator multiple times during the polymerization.
[0052] The polymerization initiator is usually used in an amount within the range of 0.001 to 5 parts by mass, preferably 0.005 to 3 parts by mass, relative to 100 parts by mass of the monomer component (a) forming the (meth)acrylic polymer (A). In addition, during the above-mentioned polymerization reaction, a polymerization initiator, a chain transfer agent, a polymerizable monomer, and a polymerization solvent may be added as appropriate.
[0053] Examples of the chain transfer agent include alkyl mercaptans such as octyl mercaptan, nonyl mercaptan, decyl mercaptan, and dodecyl mercaptan; thioglycolates such as octyl thioglycolate, nonyl thioglycolate, and 2-ethylhexyl thioglycolate; 2,4-diphenyl-4-methyl-1-pentene, 1-methyl-4-isopropylidene-1-cyclohexene, α-pinene, and β-pinene.
[0054] The chain transfer agent may be used alone or in combination of two or more.
[0055] Examples of the polymerization solvent used for solution polymerization include aromatic hydrocarbons such as benzene, toluene, and xylene; aliphatic hydrocarbons such as n-pentane, n-hexane, n-heptane, and n-octane; alicyclic hydrocarbons such as cyclopentane, cyclohexane, cycloheptane, and cyclooctane; ethers such as diethyl ether, diisopropyl ether, 1,2-dimethoxyethane, dibutyl ether, tetrahydrofuran, dioxane, anisole, phenylethyl ether, and diphenyl ether; halogenated hydrocarbons such as chloroform, carbon tetrachloride, 1,2-dichloroethane, and chlorobenzene; esters such as ethyl acetate, propyl acetate, butyl acetate, and methyl propionate; ketones such as acetone, methyl ethyl ketone, diethyl ketone, methyl isobutyl ketone, and cyclohexanone; amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; nitriles such as acetonitrile and benzonitrile; sulfoxides such as dimethyl sulfoxide and sulfolane, and the like.
[0056] The polymerization solvent may be used alone or in combination of two or more.
[0057] [Physical properties of (meth)acrylic acid polymer (A)] The glass transition temperature (Tg) of the (meth)acrylic polymer (A) is usually -80 to 0°C, preferably -70 to -10°C, more preferably -60 to -20°C, further preferably -50 to -30°C.
[0058] When Tg of the (meth)acrylic polymer (A) is within the above range, the adhesiveness and durability immediately after application tend to be excellent, which is preferred.
[0059] The Tg of the (meth)acrylic polymer (A) is calculated from the monomer units constituting the (meth)acrylic polymer (A) and their content ratios by the Fox equation.
[0060] Fox's formula: 1 / Tg = (W1 / Tg1) + (W2 / Tg2) + ... + (Wm / Tgm) W1 + W2 + ... + Wm = 1 In the above formula, Tg is the glass transition temperature of the polymer (unit: K), Tg1, Tg2, ..., Tgm are the glass transition temperatures of the homopolymers formed by each monomer (unit: K), and W1, W2, ..., Wm are the mass fractions of the structural units derived from each monomer in the entire copolymer. As the mass fraction of the structural units derived from each monomer, the feed ratio of each monomer to all monomers when synthesizing the copolymer can be used.
[0061] When calculating the Fox formula, the glass transition temperature (Tg) of a homopolymer formed from each monomer can be, for example, the value described in the Polymer Handbook Fourth Edition (Wiley-Interscience 2003).
[0062] The weight average molecular weight (Mw) of the (meth)acrylic polymer (A) measured by gel permeation chromatography (GPC method) is not particularly limited, but is usually 200,000 to 2,000,000, preferably 200,000 to 1,500,000, more preferably 200,000 to 1,000,000, and further preferably 200,000 or more and less than 800,000, in terms of polystyrene.
[0063] When the Mw of the (meth)acrylic polymer (A) is within the above range, the adhesiveness immediately after application tends to be excellent, which is preferred.
[0064] The molecular weight distribution (Mw / Mn) of the (meth)acrylic polymer (A) measured by the GPC method is usually 15 or less, preferably 10 or less, and more preferably 2-8.
[0065] [Polymer (B)] The polymer (B) has a glass transition temperature (Tg) of 30 to 200° C. and a number average molecular weight (Mn) of 500 to 10,000.
[0066] The polymer (B) used in the present composition may be one kind or two or more kinds.
[0067] The blending ratio of the polymer (B) in the present composition is 0.1 to 100 parts by mass, preferably 0.5 to 80 parts by mass, more preferably 1 to 60 parts by mass, and even more preferably 2 to 40 parts by mass, relative to 100 parts by mass of the (meth)acrylic polymer (A). If the blending ratio of the polymer (B) is within the above range, it is preferred because the adhesion immediately after application tends to be excellent.
[0068] Examples of the monomer component (b) constituting the polymer (B) in the present composition include a monomer (b1) having no crosslinkable functional group and a monomer (b2) having a crosslinkable functional group, and one or more of these can be used.
[0069] (Monomer (b1) without cross-linking functional group) The monomer (b1) having no crosslinkable functional group is a monomer having no crosslinkable functional group capable of reacting with a functional group in the crosslinking agent (C) preferably contained in the adhesive composition to form a crosslinked structure. Examples of the crosslinkable functional group include carboxyl group, hydroxyl group, amino group, amide group, and cyano group.
[0070] Specific examples of the monomer (b1) not having a crosslinkable functional group include, for example, the monomers described in the column of the alkyl (meth)acrylate (a2) whose homopolymer has a glass transition temperature of less than -55°C in the (meth)acrylic polymer (A), and the alkyl (meth)acrylate whose homopolymer has a glass transition temperature of -55°C or higher described in the column of the other monomer (a3), alicyclic group-containing (meth)acrylate, aromatic ring-containing (meth)acrylate, alkoxyalkyl (meth)acrylate, alkoxypolyalkylene glycol mono(meth)acrylate, vinyl ester, olefin, halogenated olefin, styrene-based monomer, and diene-based monomer. Among these, methyl methacrylate is particularly preferred.
[0071] The monomer (b1) not having a crosslinkable functional group may be used alone or in combination of two or more.
[0072] The content of the monomer (b1) having no crosslinkable functional group is generally 50 to 100% by mass, preferably 65 to 100% by mass, more preferably 80 to 100% by mass, and further preferably 90 to 100% by mass in 100% by mass of the monomer component (b). Within such a range, the adhesion immediately after application tends to be excellent and is therefore preferred.
[0073] (Monomer having a cross-linkable functional group (b2)) The monomer (b2) having a crosslinkable functional group is a monomer having a crosslinkable functional group that can react with a functional group in the crosslinking agent (C) preferably contained in the pressure-sensitive adhesive composition to form a crosslinked structure.
[0074] Specific examples of the monomer (b2) having a crosslinkable functional group include, for example, the monomers described in the column of the carboxyl group-containing monomer (a1) in the above-mentioned (meth)acrylic polymer (A), and the hydroxyl group-containing monomers, amino group-containing monomers, amide group-containing monomers, and cyano group-containing monomers described in the column of the other monomers (a3).
[0075] The monomer (b2) having a crosslinkable functional group may be used alone or in combination of two or more.
[0076] The content of the monomer (b2) having a crosslinkable functional group is preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 10% by mass or less in 100% by mass of the monomer component (b). Within such a range, adhesion immediately after application tends to be excellent, which is preferred.
[0077] [Method for producing polymer (B)] The polymer (B) is obtained by copolymerizing the above-mentioned monomer component (b). The production method is not particularly limited, and a known method can be used, for example, solution polymerization, bulk polymerization, emulsion polymerization, suspension polymerization, etc., and solution polymerization is preferred because the molecular weight can be easily adjusted and there are few impurities during production.
[0078] As specific production conditions, for example, the production conditions described in the column of the (meth)acrylic polymer (A) can be referred to.
[0079] [Physical properties of polymer (B)] The Tg of the polymer (B) is 30 to 200°C, preferably 40 to 175°C, more preferably 50 to 150°C, and even more preferably 60 to 125°C.
[0080] When the Tg of the polymer (B) is within the above range, excellent durability is likely to be obtained, which is preferred.
[0081] The Tg of the polymer (B) is calculated by the above-mentioned Fox formula.
[0082] The number average molecular weight (Mn) of the polymer (B) measured by the GPC method is 500 to 10,000, preferably 1,000 to 9,500, more preferably 1,500 to 9,000, and even more preferably 2,000 to 8,500 in terms of polystyrene.
[0083] When the Mn of the polymer (B) is within the above range, the adhesiveness immediately after application tends to be excellent, which is preferred.
[0084] The molecular weight distribution (Mw / Mn) of the polymer (B) measured by the GPC method is usually 10 or less, preferably 8 or less, and more preferably 2-6.
[0085] [Cross-linking agent (C)] The present composition may contain a crosslinking agent (C).
[0086] The crosslinking agent (C) is not particularly limited, and for example, an epoxy crosslinking agent, an isocyanate crosslinking agent, a metal chelate compound, etc. can be used. Among them, an epoxy crosslinking agent is preferred.
[0087] The cross-linking agent (C) used in the present composition may be used alone or in combination of two or more.
[0088] (Epoxy crosslinking agent) Examples of epoxy crosslinking agents include epoxy compounds having two or more epoxy groups in one molecule, and specifically include ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerol diglycidyl ether, glycerol triglycidyl ether, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, N,N,N',N'-tetraglycidyl meta-xylylenediamine, N,N,N',N'-tetraglycidylaminophenylmethane, triglycidyl isocyanurate, meta-N,N-diglycidylaminophenylglycidyl ether, N,N-diglycidyltoluidine, and N,N-diglycidylaniline. The number of epoxy groups in one molecule of the above epoxy compounds is, for example, 2 to 10.
[0089] (Isocyanate cross-linking agent) As isocyanate crosslinking agents, for example, isocyanate compounds having two or more isocyanate groups in one molecule can be cited. As diisocyanate compounds having two isocyanate groups in one molecule, for example, aliphatic diisocyanates, alicyclic diisocyanates, and aromatic diisocyanates can be cited. As isocyanate compounds having three or more isocyanate groups in one molecule, for example, aromatic polyisocyanates, aliphatic polyisocyanates, and alicyclic polyisocyanates can be cited. In addition, as isocyanate compounds, for example, polymers (for example, dimers or trimers, biuret bodies, isocyanurate bodies) of the above-mentioned isocyanate compounds having two or more isocyanate groups, derivatives (for example, addition reaction products of polyols and two or more diisocyanate compounds), and polymers can be cited.
[0090] (Metal Chelate Compounds) Examples of metal chelate crosslinking agents include compounds in which components such as alkoxides, acetylacetone, and ethyl acetylacetate are coordinated to polyvalent metals such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium, and zirconium. Among these, aluminum chelate compounds are preferred. Specifically, examples include aluminum isopropoxide, aluminum sec-butyrate, ethyl acetoacetate / aluminum diisopropoxide, aluminum triethylacetoacetate, and aluminum triacetylacetonate.
[0091] In the present composition, the content of the crosslinking agent (C) is usually 10 parts by mass or less, preferably 0.01 to 8 parts by mass, and more preferably 0.05 to 5 parts by mass, based on 100 parts by mass of the (meth)acrylic polymer (A).
[0092] When the content of the crosslinking agent (C) is within the above range, a crosslinked structure is formed in the pressure-sensitive adhesive layer formed from the present composition, and excellent durability is easily obtained, which is preferred.
[0093] [Solvent] The present composition may contain a solvent in order to adjust its coating properties, and an organic solvent is preferably used as the solvent.
[0094] Examples of the organic solvent include aromatic hydrocarbons such as benzene, toluene, and xylene; aliphatic hydrocarbons such as n-pentane, n-hexane, n-heptane, and n-octane; alicyclic hydrocarbons such as cyclopentane, cyclohexane, cycloheptane, and cyclooctane; ethers such as diethyl ether, diisopropyl ether, 1,2-dimethoxyethane, dibutyl ether, tetrahydrofuran, dioxane, anisole, phenylethyl ether, and diphenyl ether; halogenated hydrocarbons such as chloroform, carbon tetrachloride, 1,2-dichloroethane, and chlorobenzene; esters such as ethyl acetate, propyl acetate, butyl acetate, and methyl propionate; ketones such as acetone, methyl ethyl ketone, diethyl ketone, methyl isobutyl ketone, and cyclohexanone; amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; nitriles such as acetonitrile and benzonitrile; and sulfoxides such as dimethyl sulfoxide and cyclopentane.
[0095] The organic solvent may be used alone or in combination of two or more.
[0096] In the present composition, the content of the solvent is usually 90% by mass or less, preferably 10 to 80% by mass.
[0097] [Other ingredients] The present composition may further contain other components in addition to the above-mentioned (meth)acrylic polymer (A) and polymer (B) within a range not impairing the effects of the present invention.
[0098] When other components are used in the present composition, the other components may be one kind or two or more kinds.
[0099] Examples of other components include resin components other than the (meth)acrylic polymer (A) and the polymer (B), antistatic agents, silane coupling agents, ultraviolet absorbers, antioxidants, tackifiers, plasticizers, defoaming agents, fillers, stabilizers, softeners, pigments, and various additives such as wettability regulators.
[0100] When other components are contained, the present composition may contain them in an amount of usually 50 parts by mass or less, preferably 40 parts by mass or less, and more preferably 30 parts by mass or less, based on 100 parts by mass of the polymer (A).
[0101] [Method for producing adhesive composition for decorative film] The present composition can be produced by mixing the above-mentioned components sequentially or simultaneously by a known method.
[0102] The present composition can be prepared by mixing a (meth)acrylic polymer (A) and a polymer (B), a crosslinking agent (C) as required, a solvent, and other components by a conventionally known method. In one embodiment, for example, a polymer solution containing the (meth)acrylic polymer (A) and a polymer (B) and an organic solvent obtained when synthesizing the polymer (A) and the polymer (B) is mixed, and a crosslinking agent (C) and other components are added as required. The present composition is obtained by mixing the components at once or sequentially. The mixing time is not particularly limited, but from the perspective of operability and productivity, it is usually about 10 to 120 minutes at room temperature using a stirring device.
[0103] <Decorative film> The decorative film of the present invention comprises an adhesive layer obtained from the above-mentioned decorative film adhesive composition and a substrate layer. Preferably, the substrate layer plays a decorative role, but it may also have a decorative layer. In addition, in order to protect the adhesive layer before use, a release film may be provided on the adhesive layer. It may also further have other layers as needed.
[0104] (Adhesive layer) The adhesive layer of the decorative film according to the present invention is formed from the adhesive composition for a decorative film according to the present invention.
[0105] The adhesive layer can be obtained, for example, by applying the above-mentioned adhesive composition for a decorative film onto a substrate or a decorative layer and, if necessary, cross-linking the composition.
[0106] In order to facilitate release of bubbles between the adherend and the adhesive layer when attaching the decorative film to the adherend, the adhesive layer may have a concavo-convex shape on the surface on the side in contact with the adherend (the release film side).
[0107] The thickness of the adhesive layer is usually 3 to 500 μm, preferably 5 to 300 μm.
[0108] (Base material layer) The base material layer constitutes the outermost layer of a decorative molding obtained by attaching a decorative film to an adherend as a decoration object. The base material constituting the base material layer may be colored or colorless, and may be any of transparent, translucent and opaque. In addition, the base material layer is usually in the form of a film or a sheet, and may be a single-layer structure or a multi-layer structure.
[0109] The substrate layer is not particularly limited, but preferably contains a thermoplastic resin. Examples of the thermoplastic resin include polyvinyl chloride, polyester, polyethylene, polypropylene, polycarbonate, polymethyl methacrylate, and acrylonitrile / butadiene / styrene (ABS) resins. One or more of these may be contained.
[0110] In the base material layer, fillers such as particles, plasticizers, colorants, ultraviolet absorbers and other functional materials can be contained as needed. In addition, patterns, words and patterns for giving design properties can be printed on the surface of the base material layer, and patterns, words and patterns can also be formed inside the base material layer.
[0111] The thickness of the substrate layer is usually 10 to 1000 μm, preferably 20 to 500 μm, and more preferably 30 to 300 μm.
[0112] (Decorative layer) The decorative film of the present invention may further have a decorative layer between the substrate layer and the adhesive layer, in the substrate layer, or on the substrate layer. The decorative layer is a layer provided to give the decorative film a design property, for example, a metal layer is provided to reflect a metallic feel, and patterns, texts, and designs are reflected by printing or other methods. When a pattern is formed on the decorative layer, it can be formed by a known printing method such as gravure printing using printing ink, offset printing, screen printing, transfer printing from a transfer sheet, sublimation transfer printing, and inkjet printing. In addition, it may have a fine concave-convex shape such as an embossed pattern.
[0113] In order to express various appearance designs, the thickness of the decorative layer is usually 0.1 to 50 μm, preferably 0.5 to 40 μm, and more preferably 1 to 30 μm.
[0114] (Release film) The decorative film of the present invention may have a release film on the adhesive layer as needed. The release film is a film that protects the surface of the adhesive layer before the decorative film is actually used, and is peeled off and removed when the decorative film is used. The release film is not particularly limited as long as it is a film that can be easily peeled off from the adhesive layer, and examples thereof include resin films such as polyester films such as polyethylene terephthalate and polybutylene terephthalate, polyolefin films such as polyethylene, polypropylene, and ethylene-vinyl acetate copolymers; and paper materials such as glassine paper, kraft paper, and clay-coated paper. At least one side of the release film may be subjected to an easy-peel treatment using a release treatment agent such as a silicone-based, fluorine-based, long-chain alkyl-based, or fatty acid amide-based release treatment agent.
[0115] In addition, in order to facilitate the release of bubbles between the adherend and the adhesive layer when attaching the decorative film to the adherend, a release film with a concavo-convex shape can be used. For example, the adhesive composition can be applied to the concavo-convex surface of the release film with a concavo-convex shape and dried to form an adhesive layer, thereby transferring the concavo-convex shape to the adhesive layer, or by attaching the release film with a concavo-convex shape to the adhesive layer and transferring the concavo-convex shape to the adhesive layer, thereby giving the adhesive layer a concavo-convex shape.
[0116] The thickness of the release film is usually 10 to 500 μm, preferably 20 to 300 μm.
[0117] (Other layers) The decorative film of the present invention may have other layers as required. Examples of other layers include a protective layer, an ultraviolet absorbing layer, an antistatic layer, an impact buffer layer, etc. When other layers are present, the other layers may be one type or two or more types.
[0118] [Method for producing decorative film] The decorative film of the present invention can be obtained by, for example, the following methods: a method in which the adhesive composition for a decorative film of the present invention is applied to a release film, dried to form an adhesive layer, and the exposed surface of the obtained adhesive layer not in contact with the release film is bonded to a substrate, and maintained to form a decorative film; a method in which the present composition is applied to a substrate, dried to form an adhesive layer, and the exposed surface of the obtained adhesive layer not in contact with the substrate is bonded to a release film, and maintained to form a decorative film.
[0119] The conditions for forming the adhesive layer are as follows: The composition is applied to a release film or a substrate and dried. The drying conditions vary depending on the type of solvent, but are generally at a drying temperature of 50 to 150° C. and a drying time of 1 to 10 minutes.
[0120] Examples of the method for applying the adhesive composition include spin coating, blade coating, roll coating, bar coating, knife coating, die coating, and gravure coating.
[0121] The maintenance conditions are as follows. Maintenance is performed under an environment of usually 1 day or more, preferably 2 to 10 days, usually 5 to 60° C., preferably 15 to 50° C., usually 30 to 70% RH, preferably 40 to 70% RH. If maintenance is performed under such conditions, the adhesive layer and the substrate are sufficiently adhered. In addition, when the adhesive composition contains a crosslinking agent (C), a crosslinked body (network polymer) can be efficiently formed.
[0122] [Application of decorative film] As adherends of the decorative film of the present invention, molded articles such as articles with three-dimensional shapes can be cited, preferably articles with three-dimensional curved surfaces. Specifically, exterior and interior materials, building materials, and decorative panels of mobile bodies can be cited. It should be noted that as mobile bodies, it refers to vehicles with wheels and infinite tracks, such as passenger cars, buses, dual-mode vehicles, trucks, motorcycles, scooters, motor bicycles, bulldozers, etc.; railways such as trams, monorails, and linear electric locomotives; aircraft such as airplanes, helicopters, and drones; and ships in a broad sense.
[0123] The decorative film of the present invention has good adhesion immediately after application, so that poor adhesion such as floating and peeling is less likely to occur. Furthermore, it can exhibit sufficient durability even after application, so it is particularly preferably used as a vehicle film, specifically a vehicle exterior film (eg, a car film).
[0124] The material of the adherend is not particularly limited, and examples thereof include metal materials; wood; and plastics such as ABS resin, polycarbonate resin, polyester resin, polypropylene resin, and polyethylene resin, and the surface of the adherend may be painted.
[0125] Examples of methods for attaching a decorative film to an adherend, i.e., a molded body, include manual attachment, vacuum forming, pressurized (air pressure) forming, vacuum press forming, and hot high pressure forming. Among these, vacuum press forming is preferred because it allows for elegant decorative molding by wrapping a decorative film around the end of a molded body having a curved surface.
[0126] Example The following are specific examples that embody the disclosure of this specification. However, the disclosure of this specification is not limited to the following specific examples. It should be noted that in the following description, "parts" refer to parts by mass, and "%" refers to mass %.
[0127] [Molecular weight] The (meth)acrylic polymer (A) and the polymer (B) were subjected to gel permeation chromatography (GPC) under the following conditions to determine the weight average molecular weight (Mw) and number average molecular weight (Mn) based on standard polystyrene.
[0128] ・Measurement device: HLC-8220GPC (Tosoh Corporation) ・GPC column configuration: The following five columns (all from Tosoh Corporation) (1) TSK-GEL HXL-H (guard column) (2) TSK-GEL G7000HXL (3) TSK-GEL GMHXL (4) TSK-GEL GMHXL (5) TSK-GEL G2500HXL ・Sample concentration: 1.0 mg / cm 3 dilute with tetrahydrofuran ・Mobile phase solvent: Tetrahydrofuran ・Flow rate: 1.0cm 3 / min ・Column temperature: 40℃ [Synthesis Example 1] (Production of (meth)acrylic acid-based polymer (A1)) In a reaction apparatus equipped with a stirrer, a reflux condenser, a thermometer and a nitrogen inlet tube, 57 parts of n-butyl acrylate (BA), 15 parts of 2-ethyl acrylate (2EHA), 20 parts of methyl acrylate (MA), 8 parts of acrylic acid (AA), and 200 parts of ethyl acetate were added, and the temperature was raised to 75°C while introducing nitrogen. Next, 0.15 parts of 2,2'-azobisisobutyronitrile (AIBN) was added, and the polymerization reaction was carried out at 75-76°C for 4 hours under a nitrogen atmosphere. After the reaction was completed, the reaction solution was diluted with ethyl acetate to prepare a polymer solution with a solid content concentration of 25% by mass. The weight average molecular weight (Mw) of the obtained (meth)acrylic polymer (A1) was 450,000, and the glass transition temperature (Tg) (calculated value based on Fox's formula) was -36°C.
[0129] [Synthesis example 2] The monomer composition was changed as described in Table 1 (the unit of composition is parts by mass) and AIBN was changed to 0.1 parts. Polymerization was carried out in the same manner as in Synthesis Example 1 to obtain a (meth)acrylic polymer (A2). The Mw and Tg of the obtained (meth)acrylic polymer (A2) are shown in Table 1.
[0130] [Synthesis Examples 3 to 5] (Meth)acrylic polymers (A3) to (cA5) were obtained by polymerization in the same manner as in Synthesis Example 1 except that the monomer composition was changed as described in Table 1. Mw and Tg of the obtained (meth)acrylic polymers (A3) to (cA5) are shown in Table 1.
[0131] Table 1 BA: n-butyl acrylate 2EHA: 2-Ethylhexyl acrylate MA: Methyl acrylate AA: Acrylic acid [Synthesis Example 6] (Production of polymer (B1)) In a reaction apparatus equipped with a stirrer, a reflux condenser, a thermometer and a nitrogen inlet tube, 95 parts of methyl methacrylate (MMA), 5 parts of dimethylaminoethyl acrylate (DMAEA), 0.98 parts of N-dodecyl mercaptan (NDM) as a chain transfer agent, and 100 parts of ethyl acetate were added, and the temperature was raised to 75°C while introducing nitrogen. Next, 0.15 parts of AIBN were added, and the polymerization reaction was carried out at 75-76°C for 4 hours under a nitrogen atmosphere. After the reaction was completed, the reaction solution was diluted with ethyl acetate to prepare a polymer solution with a solid content concentration of 45% by mass. The obtained polymer (B1) had an Mw of 20,000, an Mn of 8,000, and a Tg of 105°C.
[0132] [Synthesis Example 7, Synthesis Example 9] Polymers (B2) and (cB4) were obtained by polymerization in the same manner as in Synthesis Example 6 except that the monomer composition was changed as described in Table 2 (the unit of composition is parts by mass). The Mw, Mn and Tg of the obtained polymers (B2) and (cB4) are shown in Table 2.
[0133] [Synthesis example 8] The polymerization was carried out in the same manner as in Synthesis Example 6 except that the monomer composition was changed as described in Table 2 and NDM was changed to 0.95 parts to obtain a polymer (cB3). Mw, Mn and Tg of the obtained polymer (cB3) are shown in Table 2.
[0134] Table 2 BMA: n-butyl methacrylate MMA: Methyl Methacrylate DMAEA: Dimethylaminoethyl acrylate [Example 1] The polymer solution of the polymer (B1) obtained in Synthesis Example 6 and N,N,N',N'-tetraglycidyl-m-xylylenediamine (E-AX, Soken Chemical Co., Ltd.) as a crosslinking agent were added to the polymer solution of the (meth)acrylic polymer (A1) obtained in Synthesis Example 1 and mixed to obtain a pressure-sensitive adhesive composition. The respective blending amounts were, based on solid content, 10 parts of the polymer (B1) and 0.1 parts of the crosslinking agent per 100 parts of the (meth)acrylic polymer (A1).
[0135] Next, a decorative film was produced using the obtained adhesive composition in the following manner, and the adhesion and adhesive strength were evaluated.
[0136] [Production of decorative film] As a substrate, a resin composition obtained by adding 30 parts by mass of a polyester plasticizer (ADK CIZERPN-7230, ADEKA Corporation) to 100 parts by mass of a vinyl chloride resin (ZEST1000Z, Shindai-ichi Vinyl Chloride Co., Ltd.) was extruded to prepare a soft vinyl chloride (PVC) film having a thickness of 80 μm.
[0137] Next, the adhesive composition was applied on a release-treated PET film and dried at 90° C. for 4 minutes to form an adhesive layer with a thickness of 25 μm. Then, the adhesive layer was bonded to the PVC film and aged at 40° C. for 3 days to prepare a decorative film.
[0138] [Fitness test] The obtained decorative film was placed in a vacuum press molding machine (NGF molding machine, produced by Fuse Vacuum Co., Ltd.) and a 100 mm wide x 100 mm long x 20 mm thick ABS plate was molded at a heating temperature of 110°C and a pressure of 0.2 MPa so that the elongation rate was 200%. Within 2 minutes after the decorative molding, a 5 cm long cross-shaped cut was made on the molded decorative film using a cutter and the film was placed in an environment of 23°C / 50% RH for 5 hours. The appearance of the decorative film was then evaluated based on the following criteria.
[0139] ○: No peeling or incision enlargement occurred △: No peeling occurred but the incision expanded slightly ×: Delamination or obvious enlargement of the incision occurs [Adhesion test] (Durability) The obtained decorative film was cut into pieces of 25 mm wide × 80 mm long to prepare test pieces. The peeled PET film was peeled off from the obtained test piece, and the exposed adhesive layer was attached to a stainless steel plate and pressed back and forth 3 times with a 2 kg roller. The stainless steel plate used was a stainless steel plate in which the surface of the stainless steel (SUS) 304 steel plate specified in JIS G 4305 (hereinafter referred to as the stainless steel plate) that had been BA-treated (after cold rolling and bright heat treatment) was previously degreased and cleaned with ethyl acetate. After pressing, it was placed in a 40°C / 90% RH environment for 72 hours. Then, it was placed in a 23°C / 50% RH environment for 24 hours. Next, using a tensile tester, the stainless steel plate was pulled at a peeling angle of 180° and a tensile speed of 300 mm / min at a 23°C / 50% RH environment, and the adhesion was evaluated according to the following criteria.
[0140] ○: Adhesion strength exceeds 15N / 25mm △: Adhesion force is 10~15N / 25mm ×: Adhesion force is less than 10N / 25mm [Examples 2 to 5, Comparative Examples 1 to 4] The same method as in Example 1 was used to obtain an adhesive composition except that the composition was changed as described in Table 3. It should be noted that the values described in Table 3 are solid contents. Next, decorative films were prepared using the obtained adhesive compositions in the same manner as in Example 1, and the adhesion and adhesive strength were evaluated. The results are shown in Table 3.
[0141] Table 3 As can be seen from Examples 1 to 5, by using an adhesive composition comprising a (meth)acrylic polymer (A) containing 1 to 20% by mass of a structural unit derived from a carboxyl group-containing monomer and a polymer (B) having a glass transition temperature of 30 to 200° C. and a number average molecular weight (Mn) of 500 to 10,000 as the adhesive layer of a decorative film, both the adhesion and durability immediately after application are good, and thus the adhesive composition is suitable as a decorative film.
[0142] Comparative Examples 1 and 4, which do not contain a polymer (B) having a number average molecular weight (Mn) of 500 to 10,000, show that the adhesion immediately after application is insufficient for decorative film use. In addition, Comparative Example 2, which does not contain a polymer (B) having a glass transition temperature of 30 to 200°C, and Comparative Example 3, which does not contain a (meth)acrylic polymer (A) containing 1 to 20% by mass of a structural unit derived from a carboxyl group-containing monomer, show that the durability is insufficient for decorative film use. This is believed to be due to the compatibility between the (meth)acrylic polymer (A) and the polymer (B).
[0143] Industrial Applicability The adhesive composition for decorative films of the present invention is suitable for forming an adhesive layer of a decorative film. The decorative film of the present invention is suitable for surface decoration of molded bodies such as exterior and interior materials of mobile bodies, building materials, decorative panels, etc. Specifically, it can be preferably used as a vehicle exterior film such as a car film.
Claims
1. A decorative film adhesive composition comprising a (meth)acrylic acid-based polymer (A) containing 1% by mass to 20% by mass of a structural unit derived from a carboxyl group-containing monomer, and A polymer (B) having a glass transition temperature of 30 to 200° C. and a number average molecular weight Mn of 500 to 10,000, The polymer (B) is contained in an amount of 0.1 to 100 parts by mass based on 100 parts by mass of the (meth)acrylic polymer (A).
2. The adhesive composition for decorative films according to claim 1, wherein The (meth)acrylic polymer (A) contains 6.5% by mass to 20% by mass of a structural unit derived from an alkyl (meth)acrylate having a homopolymer glass transition temperature of less than -55°C.
3. The adhesive composition for decorative films according to claim 1, wherein The weight average molecular weight Mw of the (meth)acrylic polymer (A) is 200,000 or more and less than 800,000.
4. The adhesive composition for decorative films according to claim 1, wherein The polymer (B) contains 65% by mass or more of a structural unit derived from methyl methacrylate. 5 . A decorative film comprising an adhesive layer formed from the adhesive composition for a decorative film according to claim 1 , and a substrate layer. The decorative film according to claim 5 , which is used for vacuum pressure forming.
Citation Information
Patent Citations
Decorative film and decorative molding having the same
JP2019112574A